Estrategias en seguridad y salud ocupacional para la reducción de accidentes en empresas mineras - Loayza Susanibar, Guido Francisco (2023)
The study focused on evaluating the effect of behavioral change strategies, supervisory leadership, and investment in occupational health and safety in reducing accidents in mining companies; For this, an investigation of a quantitative approach, of an experimental type, was carried out, where the Sierra Antapite mining unit in the department of Huancavelica was taken as a case study. The following were used as a research instrument: the survey and observation, through knowledge evaluations in SST, affectivity level evaluations, registration of planned work observations, and the preparation and execution of a budget destined for Capex and Opex in turn aligned mainly in the implementation of controls that allow managing occupational health and safety; A sample of 123 workers was considered. The results determined that in 2022, it is obtained that accidents are reduced by 58% compared to the year 2021. The conclusions determined that the behavioral change strategies, Supervision Leadership and Investment in OSH have an effect on the reduction of accidents In addition, it has a positive impact on the indicators of frequency, severity and occupational health and safety accidents in mining companies.